2016
DOI: 10.3386/w22508
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Black Box of the Matching Function: the Power of Words

Abstract: On the leading job board CareerBuilder.com, high-wage job postings unexpectedly attract fewer applicants. This negative relationship holds even within detailed occupations.In our directed search model, high-wage jobs attract fewer applicants only if applicants are heterogeneous. However, if there is no applicant heterogeneity, high-wage jobs attract more applicants. Empirically, job title heterogeneity is key: controlling for job titles, jobs with 10% higher wages do attract 7.7% more applicants. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Going from the 25th percentile of market concentration to the 75th percentile of market concentration is associated with a decline in wages of 5% using specification (3), and of 17% using specification (6), our baseline specification for the IV. 5 Marinescu and Wolthoff (2016) showed that job titles are an important predictor of wages and are informative about the type of job and required skills beyond a pure wage-signalling effect. We are thus interested in studying to what extent market concentration affects wages through job titles and to what extent it has a direct effect beyond the effect that can be explained by job titles.…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Going from the 25th percentile of market concentration to the 75th percentile of market concentration is associated with a decline in wages of 5% using specification (3), and of 17% using specification (6), our baseline specification for the IV. 5 Marinescu and Wolthoff (2016) showed that job titles are an important predictor of wages and are informative about the type of job and required skills beyond a pure wage-signalling effect. We are thus interested in studying to what extent market concentration affects wages through job titles and to what extent it has a direct effect beyond the effect that can be explained by job titles.…”
Section: Regression Resultsmentioning
confidence: 99%
“…We perform a number of additional robustness checks. Most importantly, Marinescu and Wolthoff (2016) show that posted wages are largely explained by job titles. Therefore, it is important to control for heterogeneity by job title to get an estimate of the impact of concentration on wages for a given job type.…”
Section: Introductionmentioning
confidence: 97%
“…Our work is also related to models of labor market search that allow for a notion of search intensity (Costain, 1997;Pissarides, 2000;Shimer, 2004;Christiansen et al, 2005; among others). Finally, our paper is related to the growing literature that studies online job search (e.g., Kuhn and Skuterud, 2004;Kroft and Pope, 2014;Brown and Matsa, 2012;Kudlyak, Lkhgvasuren, and Sysuyev, 2013;Marinescu and Wolthoff, 2015), and to the literature that studies hiring and vacancies (Barron, Bishop, and Dunkelberg, 1985;Holzer, Katz, and Krueger, 1991;Davis, Faberman, and Haltiwanger, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One quite remarkable feature of our data is that we are able not only to explore outcomes for aggregate conditions at the local level, but also to track outcomes for individual positions. Previous research has shown that most of the variation in posted wages and in the experience and education level of applicants is explained by job titles (Marinescu and Wolthoff 2015). Thus, controlling for job title by firm demonstrates that employers decrease requirements for the same job title in response to the declining availability of workers.…”
Section: Controlling For Changes In Employer Composition and Data mentioning
confidence: 99%
“…Previous research has shown that most of the variation in posted wages and in the experience and education level of applicants is explained by job titles (Marinescu and Wolthoff 2015).…”
Section: Empirical Approachmentioning
confidence: 99%